PENGARUH DESENTRALISASI FISKAL, DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DAN PENDAPATAN ASLI DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING DI 12 KABUPATEN/KOTA SE-PROVINSI RIAU - Zaufi, Muhammad Yafiz; Taufik, Taufeni; Agusti, Restu (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
Indonesia's national development indeed according to guidelines which are thentranslated into Repelita is development that embraces the concept of humandevelopment. The concept of integral human development is a concept thatrequires improving the quality of life of the population both physically andmentally and do focused on human resource development physically and mentallyimplies an increase in the basic capacity of the population will then increase theopportunity to participate in the development process berkelanjutan.Azas equity isone of the trilogy of development that will be implemented in a variety ofdevelopment programs, is one of the principles of human development. Througheight lanes equalization strategy, policy development led to the partiality of thedisadvantaged population groups. Along with economic growth, an increase inphysical and mental quality of the population by the government through thedevelopment in the field of education and basic health research was conducted in12 districts / cities in Riau Province. Showing how the Human Development Indexin Riau if it goes well or not, and in this study was associated also with the FiscalDecentralization, General Allocation Fund, Special Allocation Fund and Incomenative areas affected by expenditure Capital Thus, in this study can findprosperity in Every District and City in the province of Riau. So in Riau Provincegovernment can measure a year in the future so that all funds were used on targetand no irregularities or inequities in the use of funds in Riau Province.